Science World [motion pictures] Atmospheric science : global forcasting; - winds and air currents; - weather systems in motion. - Coronet (Northbrook, IL Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol. 16: Global forcasting; - Winds and air currents; - Weather systems in motion
Original copy in VHS format (VHS 16)
[Distributed by] International Book Center, Philippines
Keywords: Winds; Weather Systems; Forecasting